Zambia : An Assessment of the Investment Climate - World Bank (Washington, DC, 2013)
This Zambia Investment Climate Assessment (ICA) forms part of World Bank Group global initiative to systematically analyze conditions for private investment and enterprise growth. Improving the investment climate is recognized as a key pillar of developing countries' path to promote economic growth and reduce poverty. The I C A compliments and amplifies a series of diagnostic work on this issue being undertaken by the World Bank Group in collaboration with the Government of Zambia. Throughout this report, empirical results showing the relative position of Zambia versus potential competitors will be presented. To understand the quality of investment climate in Zambia from the perspective of the private sector, the report draws on the results of a firm survey conducted in 2003, covering a sample of more than 200 service and manufacturing firms, large and small, located in different parts of Zambia.' This Investment Climate Assessment has three key parts: Empirical analysis of productivity; examination of investment climate constraints; and strategy for improving the investment climate and productivity. The report contains ordered recommendations in five key areas: Macroeconomics and finance, public-private sector interactions, infrastructure, labor market issues, and rule of law.